The Role of Integrated Health Informatics in Streamlining Patient Flow from Emergency Department to Admission: A Review of Administrative and Clinical Synergies - Almarwani, Majed Salah; Salha Ahmed Mohammed Osis; Ghosoon Ahmad Mohd Osis; Fatimah Mohammed; Khaled Mohammed Alharbi; Abdulaziz Ali Abdulaziz Aldobayan; Mohammed Fahad Mohammed Hawbani; Ramzi Hassan Ahmed Julayhi; Samir Ahmed Hassan Alwadani; Abdulrahman Ahmed Mohammed Maslmani; Hayfaa Mohammed Saad Shuraidh; Bashayr Radhi Alwan Aldhafeeri (Saudi Journal of Medicine and Public Health, 2024)
Background: Emergency Department (ED) overcrowding and hospital-wide patient flow blockages represent a critical challenge for healthcare systems globally, impacting patient safety, staff well-being, and organizational efficiency. The journey from ED triage to inpatient admission is a complex, multi-stakeholder process prone to delays and communication failures. Aim: This narrative review synthesizes contemporary literature (2010-2024) to examine how integrated health informatics—spanning Electronic Health Records (EHRs), patient tracking systems, and interoperable platforms—facilitates administrative and clinical synergies to streamline patient flow from the ED to admission. Methods: A systematic search was conducted across PubMed, CINAHL, Scopus, and ProQuest databases, identifying peer-reviewed articles, systematic reviews, and seminal reports. Results: Findings reveal that interoperable health informatics enhances real-time visibility, improves interprofessional communication, and supports data-driven decision-making. Successful implementation is shown to reduce ED length of stay (LOS), left-without-being-seen (LWBS) rates, and ambulance diversion. Crucially, it transforms roles, particularly for nursing and unit secretaries, shifting them towards proactive flow coordination. However, significant barriers persist, including interoperability limitations, workflow misalignment, and training deficits. Conclusion: Integrated health informatics is indispensable for modern patient flow management, creating synergistic "command centers" that bridge clinical and administrative functions. Future success hinges on human-centered design, robust change management, and viewing informatics not as a mere tool but as the foundational architecture for a resilient, patient-centered healthcare system.